2021
DOI: 10.1007/s10549-021-06153-3
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant endocrine therapy use in early stage breast cancer during the covid-19 pandemic

Abstract: Purpose Physician treatment preferences for early stage, estrogen positive breast cancer (ER + BC) patients were evaluated during the initial surge of the COVID-19 pandemic in the US when neoadjuvant endocrine therapy (NET) was recommended to allow safe deferral of surgery. Methods A validated electronic survey was administered May–June, 2020 to US medical oncologists (MO), radiation oncologists (RO), and surgeons (SO) involved in clinical trials organizations. Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…A special attention should be posed towards men and women under hormonal therapy for prostate and mammary cancer, a therapy that most physician preferred during the pandemic to allow safe deferral of surgery [84].…”
Section: Femalesmentioning
confidence: 99%
“…A special attention should be posed towards men and women under hormonal therapy for prostate and mammary cancer, a therapy that most physician preferred during the pandemic to allow safe deferral of surgery [84].…”
Section: Femalesmentioning
confidence: 99%
“… 20 In a June 2020 survey of US-based oncologic providers, 12% (13) of providers reported that they routinely used NET pre-COVID-19, while a reported 53% (114) of providers reported they would use short-term NET pre-surgically during COVID-19. 21 Another provider survey by the European Breast Cancer Research Association reported that 68% (255) of physicians recommended endocrine therapy for luminal A tumors to enable surgery to be postponed during the pandemic. 22 In randomized trials, NET has been shown to be safe and effective in increasing the rates of breast-conservation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment approach permitted delays in surgical resection until additional personal protective equipment (PPE) and other resources could be obtained and specific COVID-19 hospital protocols implemented. 1 Genomic testing on core biopsy specimens versus surgical specimens was also utilized to determine which patients were more suitable for neoadjuvant chemotherapy (NCT) or NET. Telemedicine allowed a pathway where the doctor–patient encounter could occur without additional COVID-19 risks, but could it be successfully implemented with a new breast cancer diagnosis?…”
Section: Currentmentioning
confidence: 99%